ESTUDIO PRELIMINAR DEL COMPLEJO PARASITICO DE PHYTOLIRIOMYZA JACARANDAE (DIPTERA: AGROMYZIDAE), EN JACARANDA MIMOSIFOLIA (BIGNONIACEAE) EN CORDOBA, ARGENTINA - Salvo, Adriana; Valladares, Graciela (Acta Entomológica Chilena, 2022)
A population of Phytoliriomyza jacarandae Steyskal & Spencer, was sampled monthly from April 1991 through April 1992 in a seminatural park in Córdoba, Argentina. Adults were reared, identified and counted, which allowed characterization of the parasitoid complex, and quantification of the parasitism along the year. Eight parasitoid species were recorded, of which six are mentioned for the first time parasitizing P. jacarandae. Proacrias sp and Diglyphus websteri (Crawford) were the dominant species. Total percentage parasitism on each date was related to host abundance on the previous sampling date, and to parasitoid species richness.